Ectoparasites associated with sigmodontine rodents from northeastern Argentina - Lareschi, Marcela; Savchenko, Ekaterina; Urdapilleta, Mara (THERYA, 2019)
Usually sigmodontine rodents (Cricetidae) are associated with a variety of ectoparasites. However, the studies in northeastern Argentina are scarce. Herein we analyze the ectoparasite component communities associated with four species of sigmodontines in the south of the Province of Misiones. In total, 835 ectoparasites were collected from the 97 rodents examined: 782 mites (Acari, Mesostigmata; S = 7; P = 78.35 %; MA = 8.06), 50 fleas (Hexapoda, Siphonaptera; S = 2; P = 21.65%; MA = 0.53), and two ticks (Acari, Ixodida; S = 1; P = 2.06 %; MA = 0.02, P < 0.005). The following five species are mentioned for the first time for the northeastern: Androlaelaps rotundus, Gigantolaelaps wolffsohni, Laelaps manguinhosi, L. paulistanensis, and Polygenis (P.) tripus, increasing the biodiversity known for the area. A tendency toward host aggregation was observed for most of the ectoparasites. Out of 10 ectoparasite species identified in the present study, five were collected from a unique host species, and so, species richness varied between three and four in every component community. Since some of the ectoparasites identified may play a role as vectors of pathogens, the obtained results contribute to a better understanding of the ectoparasite-host relationship, which may have epidemiological implications.